Pengaruh Keragaman Produk Dan Digital Marketing Terhadap Minat Beli Konsumen Pada Ms Glow Di Kota Langsa - Wahyuni, Rahmi; Lindung Bulan, Tengku Putri; Amilia, Suri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to determine the effect of product diversity and digital marketing on consumer buying interest at MS GLOW in Langsa City.  This study used a sample of 96 respondents who used MS GLOW products in Langsa City.  This study uses a quantitative approach obtained by distributing questionnaires using a Likert scale.  The method used is multiple linear regression equation, t test, F test and coefficient of determination test.  The results of the t test prove that product diversity has a significant effect on buying interest, digital marketing has a significant effect on buying interest at MS GLOW in Langsa City.  The results of the F test state that product diversity, and digital marketing have a significant effect on buying interest at MS GLOW in Langsa City.  The result of the coefficient of determination test (Adjusted R²) has a value of 0.368 or 36.8% affecting the buying interest of MS GLOW in Langsa City.  While 63.2% is influenced by other variables not examined such as price quality, promotion, brand image.